Gastrointestinal stromal tumors (GIST) of the anus: A single institution experience - Scow, Jeffrey S.; Mathis, Kellie L. (Turkish Journal of Gastroenterology, 2019)
Abstract Cite this article as: Scow JS, Mathis KL. Gastrointestinal stromal tumors (GIST) of the anus: A single institution experience. Turk J Gastroenterol 2019; 30(6): 576-7